Antimicrobial activity of dragon's eye (dimocarpus logan) leaf methanolic crude extract on staphylococcus auereus, escherichia coli, and saccharomyces crevisiae - Keren Avery D. Andres, Karen Kaye D. Ballesteros, Micah Skekainah R. Gile, Rovic Vincent D. Gutierrez 4 0 16; 5
ABSTRACT: Emergence of drug-resistant microorganisms posed a significant challenge to the healthcare industry which led to the demand for alternative antimicrobial materials. The main objective of this study is to investigate the antimicrobial properties of Dragon's eye (Dimocarpus longan) leaf methanolic crude extract against Staphylococcus aureus, Escherichia coli, and Saccharomyces cerevisiae. Leaves of D. longan and the positive control Guava (Psidium guajava) were prepared. dried, and extracted using a rotary evaporator. Phytochernical constituents of D. longan revealed presence of alkaloids, flavonoids, glycosides, and terpenoids. Disc diffusion method determined the antimicrobial effect of D. longan at 250mg/ml by measuring zones of inhibition (ZOl) produced. Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were performed through a series of tube dilution assays. One-way ANOVA was applied to analyze statistical significance among ZOls of different concentrations and one tailed T-test was employed to compare the most effective group of D. longan to P. guajava, both at a<0.05. Results showed that D. longan possessed a partially active antimicrobial activity with S. aureus while no ZOis were produced in E.coli, and S. cerevisiae. MIC and MBC of S. aureus were reported to be 62.5 mg/ml and 125 mg/ml, respectively. One-way ANOVA showed to have a significant difference among the different concentrations. As a result, a post-hoc test was utilized and determined that the 2 highest concentrations have a similar effect on S. aureus. One-tailed T-test revealed that there is a significant difference between the most effective concentration in D. longan and P. guajava. Keywords: antimicrobial activity, Dimocarpus longan, minimum bactericidal concentration, minimum inhibitory concentration, phytochemical analysis, zone of inhibition
Undergraduate Thesis: (Bachelor of Science in Biology) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2